2022
DOI: 10.1111/obr.13493
|View full text |Cite
|
Sign up to set email alerts
|

How high‐fat diet affects bone in mice: A systematic review and meta‐analysis

Abstract: High-fat diet (HFD) feeding for mice is commonly used to model obesity. However, conflicting results have been reported on the relationship between HFD and bone mass. In this systematic review and meta-analysis, we synthesized data from 80 articles to determine the alterations in cortical and trabecular bone mass of femur, tibia, and vertebrae in C57BL/6 mice after HFD. Overall, we detected decreased trabecular bone mass as well as deteriorated architecture, in femur and tibia of HFD treated mice. The vertebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 186 publications
0
11
0
Order By: Relevance
“…It has been reported that estrogen level leads to critical differences in inflammation and bone mass of obese individuals. 10,87,88 Male mice display more pronounced inflammation with obviously elevated proinflammatory cytokines especially TNF-α and suffer more severe trabecular bone loss than females after a long-term high-fat diet. 10,89 Besides, there is a potential correlation between body weight and estrogen levels in females.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that estrogen level leads to critical differences in inflammation and bone mass of obese individuals. 10,87,88 Male mice display more pronounced inflammation with obviously elevated proinflammatory cytokines especially TNF-α and suffer more severe trabecular bone loss than females after a long-term high-fat diet. 10,89 Besides, there is a potential correlation between body weight and estrogen levels in females.…”
Section: Discussionmentioning
confidence: 99%
“…10,87,88 Male mice display more pronounced inflammation with obviously elevated proinflammatory cytokines especially TNF-α and suffer more severe trabecular bone loss than females after a long-term high-fat diet. 10,89 Besides, there is a potential correlation between body weight and estrogen levels in females. 90 Therefore, if females were used, estrogen level would be a profound factor affecting bone health and serum TNF-α levels in rats thus greatly increasing research difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 The metabolic syndrome is not merely a superimposition of multiple chronic conditions but an integrative state where such conditions act in a synergistic manner to produce deleterious systemic effects, including effects on bone homeostasis. 4 Bone tissue has multiple vital functions, such as support, protection, and hematopoiesis. Bone homeostasis is maintained by the balance of osteoblast and osteoclast activities, and breaking this balance will lead to a series of bone diseases.…”
Section: Introductionmentioning
confidence: 99%